Does somatosensation change with age in children and adolescents? A systematic review. (28th July 2016) - Taylor, S.; McLean, B.; Falkmer, T.; Carey, L.; Girdler, S.; Elliott, C.; Blair, E.
Abstract: Background: Somatosensory modalities, such as touch, proprioception and haptic ability, greatly influence the achievement of developmental milestones for children. Describing somatosensory impairment, natural variability and typical or expected developmental changes across age groups will help establish frameworks for intervention in clinical populations. This systematic review aimed to determine how different somatosensory modalities develop across childhood into adolescence to use as a point of reference for children at risk of somatosensory impairment. Methods: Searches of five electronic databases were undertaken through EBSCO‐host (MEDLINE, CINAHL, PsycINFO, SPORTDiscus and ERIC) for studies measuring at least one somatosensory modality in typically developing individuals between birth and 18 years and analysed by age. Characteristics of studies were collected including country of origin, sample size, demographics and outcome measure used. Quality assessment and data extraction were performed by two independent reviewers. Results: Twenty three cross‐sectional studies were included from a total of 188 articles retrieved: 8 examined aspects of touch, 5 proprioception and 10 haptic ability. Variability of study designs and variation in assessment tools precluded any formal meta‐analysis. Conclusions: Somatosensation matures through childhood into adolescence; however, the present review found the pattern of somatosensory development varied depending on the assessment tool used and the aspect of somatosensation being measured, making it difficult to describe typical performance. There is a need for comprehensive assessment batteries to measure the somatosensation, including touch, proprioception and haptic ability, of children at risk of somatosensory impairment to aid in the development of effective interventions.